Performance enhancement of trapezoidal salt gradient solar ponds using reflectors and glazing - Vinoth Kumar, J.; Venkatesan, M.; Prakash, K. B.; Bharathiraja, R.; Hussain, Fayaz; Gulbarga, Mohammad Imtiyaz; Alam, Mohammad Mukhtar; Keçebaş, Ali (Elsevier, 2025)
Salt gradient solar ponds represent a sustainable and cost-effective technology for storing low-grade thermal energy, yet their geometric and optical enhancement strategies remain insufficiently explored. This study experimentally and numerically investigates the thermal and exergy performance of a novel trapezoidal salt gradient solar pond equipped with east–west oriented reflectors and a transparent glass cover. Two identical systems were constructed under the same outdoor conditions: a conventional pond and a reflector-enhanced pond. A validated one-dimensional, time-dependent thermal model based on finite difference methods was used to simulate the vertical stratification within the upper, non-convective, and lower convective layers. The reflector-integrated system achieved a 26.43 % increase in bottom-layer temperature, reaching 68.64 °C, with temperature gradients enhanced by 32.73 % and 11.24 % in the upper and middle layers, respectively. The energy efficiency of the lower, middle, and upper zones improved by 52.6 %, 48.6 %, and 35.8 %, while exergy efficiency increased from 0.93 % to 1.46 %. The inclusion of reflectors boosted solar radiation capture by 46.4 %, and the glass cover reduced thermal fluctuations and shortened the stabilization period by approximately 25 %. Overall, the combined reflector-glazing configuration enhanced both the quantity and quality of stored thermal energy through higher temperature ratios and reduced entropy generation. This study provides the first experimentally validated hybrid trapezoidal solar pond integrating geometric, optical, and insulation-based improvements, offering a scalable and efficient approach for sustainable low-temperature heat storage and renewable energy utilization.